2016
DOI: 10.1080/13557858.2016.1263286
|View full text |Cite
|
Sign up to set email alerts
|

Severity of household food insecurity and lifetime racial discrimination among African-American households in South Carolina

Abstract: Severity of household food insecurity is associated with lifetime racial discrimination among African-American households in South Carolina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 53 publications
6
58
2
2
Order By: Relevance
“…It is possible that racial discrimination and racism play a role in creating food inequalities across racial/ethnic groups. For example, Burke et al [31] investigated the association between lifetime racial discrimination and food insecurity among Black food-insecure households with children in South Carolina. They found that even after adjusting for other demographic and socioeconomic confounders, every unit increase in the frequency of racial discrimination was associated with a 5% increase in the odds of being very low food secure [31].…”
Section: Race/ethnicity and Household Food Insecuritymentioning
confidence: 99%
“…It is possible that racial discrimination and racism play a role in creating food inequalities across racial/ethnic groups. For example, Burke et al [31] investigated the association between lifetime racial discrimination and food insecurity among Black food-insecure households with children in South Carolina. They found that even after adjusting for other demographic and socioeconomic confounders, every unit increase in the frequency of racial discrimination was associated with a 5% increase in the odds of being very low food secure [31].…”
Section: Race/ethnicity and Household Food Insecuritymentioning
confidence: 99%
“…Social epidemiologists and public health scholars have long argued that racial differences in economic outcomes are manifestations of structural racism, and are powerful in shaping racial disparities in health (49)(50)(51). Scholars in the US have also established a potential relationship between racial discrimination and an elevated risk of food insecurity (22)(23)(24)(25). In their study of African-American food-insecure households with children, Burke et al (2018) found that even after adjusting for socio-demographic factors, a one-unit increase in the frequency of lifetime racial discrimination was associated with a 5% increase in the odds of very low food insecurity (22).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars in the US have also established a potential relationship between racial discrimination and an elevated risk of food insecurity (22)(23)(24)(25). In their study of African-American food-insecure households with children, Burke et al (2018) found that even after adjusting for socio-demographic factors, a one-unit increase in the frequency of lifetime racial discrimination was associated with a 5% increase in the odds of very low food insecurity (22). Odoms-Young and Bruce argue that in order to address racial disparities in food insecurity, interventions should target structural racism as well as class inequality (52).…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, dalam hal pengolahan data, metode HFIAS juga lebih sederhana dan mudah karena jawaban dari responden langsung diskoring kemudian dikategorikan, sedangkan metode Maxwell lebih rumit karena terlebih dahulu harus menghitung tingkat pengeluaran pangan dan konsumsi energi per unit ekivalen dewasa kemudian kedua indikator tersebut digabungkan untuk mengkategorikan tingkat ketahanan pangan. HFIAS merupakan alat sederhana dan valid untuk mengukur ketahanan pangan rumah tangga yang mengukur komponen akses dalam hal ketersediaan pangan di tingkat rumah tangga 3,[5][6][7][8][9][10][11][20][21][22][23][24][25] . Hal ini sejalan dengan penelitian Pardede dan Pandiangan bahwa survey dengan metode HFIAS ini dinilai sangat baik digunakan untuk mendapatkan basis data ketidaktahanan pangan, mudah dilakukan untuk mendapatkan perkembangan status ketahanan pangan baik masing-masing rumah tangga, kelompok ataupun populasi di daerah kewilayahan tertentu.…”
Section: Uji Validitas Secara Kualitatifunclassified
“…Penelitian Gizi dan Makanan, Juni 2019 Vol. 42(1):[11][12][13][14][15][16][17][18][19][20] [dikosongkan]…”
unclassified